Music and the Emotions: The Philosophical Theories - Budd, Malcolm (London Routledge & Kegan Paul, 1985)
The most fundamental debate in the philosophy of music involves the question of whether there is an artistically important connection between music and the emotions. Many theories of the nature and significance of music as an art form have maintained that at least one important value of music is its capacity to represent, express, communicate, or symbolize a variety of extra-musical emotions or a certain aspect of emotion. Yet these theories are rejected by those who believe that the value of any musical work is specifically musical, and accordingly must be independent of any relationship between music and the emotions. Now in paper,Music and the Emotionspresents and critically examines the chief theories about the relationship between music and the emotions. These theories include those of Eduard Hanslick, Edmund Gurney, Carroll Pratt, Arthur Schopenhauer, Susanne Langer and Leonard Meyer.
Keywords: Music philosophy and esthetics; Emotion